PENGARUH BEAUTY INFLUENCER, ULASAN KONSUMEN DARING DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK MAYBELLINE - Rohmah, Annisa Nurul (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
Influencer,Online Consumer Review, Product Quality toward Purchase Intention on Maybelline product. The method used in this research is quantitative. The object of research is Maybelline brand with a population of all Maybelline consumer with a sample of 180 respondents. It is calculated based on the Structural Equation Modeling (SEM) formula. The sampling method used purposive sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis method using Partial Least Square. This study proves that beauty influencer has a negative effect and not significant on purchasing intention for Maybelline product, online consumer reviews has a positive and significant effect on purchasing intention for Maybelline product and product quality has a positive and significant effect on purchasing intention for Maybelline product.